1998
DOI: 10.1152/ajplung.1998.274.1.l39
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine regulation of ozone-induced neutrophil and monocyte inflammation

Abstract: Pulmonary inflammation has been observed in humans and in many animal species after ozone exposure. Inflammatory cell accumulation involves local synthesis of chemokines, including neutrophil chemoattractants such as macrophage inflammatory protein-2 (MIP-2), and monocyte chemoattractants, such as monocyte chemoattractant protein-1 (MCP-1). To better understand the mechanism of ozone-induced inflammation, we exposed mice and rats to ozone for 3 h and measured MIP-2 and MCP-1 gene expression. In C57BL/6 mice, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
48
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 29 publications
7
48
1
Order By: Relevance
“…Exposure of animals to O 3 has been shown to increase monocyte chemotactic activity in bronchoalveolar fluid (21). This activity was inhibited by an Ab directed against CCL2 in a monocyte chemotaxis assay (21).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Exposure of animals to O 3 has been shown to increase monocyte chemotactic activity in bronchoalveolar fluid (21). This activity was inhibited by an Ab directed against CCL2 in a monocyte chemotaxis assay (21).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhao et al (21) reported that 2 ppm O 3 induced CXCL1,2,3 (MIP-2) mRNA expression that peaked 4 h postexposure, whereas CCL2 mRNA levels peaked at 24 h postexposure. In the present study, the CXCL1,2,3 (KC and MIP-2), CXCL10, CCL3, CCL7, and CCL11 were up-regulated at 0 h postexposure, whereas only CCL3, CCL7, and CXCL10 were still up-regulated 18 h postexposure, indicating differences in the kinetics of different chemokine expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations